If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2w+6=5w+3
We move all terms to the left:
2w+6-(5w+3)=0
We get rid of parentheses
2w-5w-3+6=0
We add all the numbers together, and all the variables
-3w+3=0
We move all terms containing w to the left, all other terms to the right
-3w=-3
w=-3/-3
w=1
| 18+3h=-11-10 | | Y=900x,x=0.027 | | 244=94+a | | 7(8n-1)=19+32 | | 3x+18=6x-15 | | -9x+-12=6 | | 3(1-3x)=2+(-4x+7) | | 〖36x〗^2-8x-5=0 | | 2/3x+11/6=11/14 | | -9x+12=6 | | -9(v-2)=6v-27 | | Mx7=21 | | 1/3x+5=1/3x+39 | | 10-18x=-1 | | U+15=-20-4u | | 12u-6+6=30+6 | | -9−1x=9−7x | | 6/15=10x | | 19-2j=17 | | S+1=2s-20 | | 4.2g+3=2.2g+13 | | -6x+30=-4(x-8) | | 2+4.8=s | | b+61/3=-4 | | -x/9=-50 | | -2y+11=6y+35 | | h-2/3=6 | | -17p=-16p+20 | | 22=d/2+17 | | -9−1p=9−7p | | 25=-7w+3(w+3) | | 12u-6=-30 |